Freeze-thaw cycles alter soil hydro-physical properties and dissolved organic carbon release from peat - Liu, Haojie; Rezanezhad, Fereidoun; Zak, Dominik; Li, Xiujun; Lennartz, Bernd (Frontiers in Environmental Science, 2022)
The ongoing climate warming is likely to increase the frequency of freeze-thaw cycles (FTCs) in cold-temperate peatland regions. Despite the importance of soil hydro-physical properties in water and carbon cycling in peatlands, the impacts of FTCs on peat properties as well as carbon sequestration and release remain poorly understood. In this study, we collected undisturbed topsoil samples from two drained lowland fen peatlands to investigate the impact of FTCs on hydro-physical properties as well as dissolved organic carbon (DOC) fluxes from peat. The soil samples were subject to five freeze-thaw treatments, including a zero, one, three, five, ten cycles (FTC0, FTC1, FTC3, FTC5, and FTC10, respectively). Each FTC was composed of 24 hours of freezing (−5°C) and 24 hours of thawing (5°C) and the soil moisture content during the freeze-thaw experiment was adjusted to field capacity. The results showed that the FTCs substantially altered the saturated hydraulic conductivity (Ks) of peat. For peat samples with low initial Ks values (e.g. < 0.2×10–5 m s–1), Ks increased after FTCs. In contrast, the Ks of peat decreased after freeze-thaw, if the initial Ks was comparably high (e.g. > 0.8×10–5 m s–1). Overall, the average Ks values of peatlands decreased after FTCs. The reduction in Ks values can be explained by the changes in macroporosity. The DOC experiment results revealed that the FTCs could increase DOC concentrations in leachate, but the DOC fluxes decreased mainly because of a reduction in water flow rate as well as Ks. In conclusion, soil hydraulic properties of peat (e.g. Ks) are affected by freezing and thawing. The dynamics of soil hydraulic properties need to be explicitly addressed in the quantification and modelling of the water flux and DOC release from peatlands.